Barthes and Antonioni in China: the muffling of criticism. Issue 2 (23rd February 2016) - O'Meara, Lucy
Abstract : This article examines Michelangelo Antonioni's documentary film Chung Kuo – Cina (1972) alongside the texts written by Roland Barthes during and after his trip to China with the Tel Quel group in 1974. Antonioni and the Tel Quel travellers had very similar experiences in China: their itinerary was tightly controlled and they were supervised at all times by Communist party officials while visiting officially sanctioned sights. The article will argue that Barthes's China writings are strongly influenced by Antonioni's film, and mount a very similar form of oblique critique of the Maoist state. However, it will be seen that there is a disjuncture between Barthes's published text on the China trip ('Alors, la Chine?', published in Le Monde after his return from China) and the recent, posthumously published notebooks and teaching notes on China ( Carnets du voyage en Chine [ Travels in China ] and the 1974 'Account of the trip to China'). The posthumous texts articulate a strong ideological critique of the Maoist state which Barthes does not allow to filter through to 'Alors, la Chine?' This muffling of criticism is in part due to the self-censorship implied by Barthes's enmeshing of his public persona, as well as his private friendships, with the Tel Quel project.